Heat equation and wave equation with general stochastic measures - Radchenko, V. N. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We consider the heat equation and wave equation with constant coefficients that contain a term given by an integral with respect to a random measure. Only the condition of sigma-additivity in probability is imposed on the random measure. Solutions of these equations are presented. For each equation, we prove that its solutions coincide under certain additional conditions.